Curcumin and multiple health outcomes: critical umbrella review of intervention meta-analyses - Xu, Qin; Lian, Hua; Zhou, Rui; Gu, Zhenzhen; Wu, Jiao; Wu, Yu; Li, Zhongyu (Frontiers in Pharmacology, 2025)
ObjectiveThis review aimed to determine the therapeutic effects and safety of oral curcumin compared with other comparators for human health and wellbeing outcomes.MethodsPubMed, Embase, and Cochrane Library were searched from their inception to 18 June 2024. The Assessment of Multiple Systematic Reviews-2 checklist, and Grading of Recommendations, Assessment, Development and Evaluation system were used to assess the methodological and evidence quality for each meta-analysis, respectively. The results are presented in a narrative review.ResultsWe included 25 studies. The overall methodological quality was relatively poor, and there is considerable room for improvement. The findings suggest that curcumin has potentially positive effects on lipid profiles, blood pressure, inflammatory markers and oxidative stress, musculoskeletal diseases, emotional and cognitive function, ulcerative colitis, liver and kidney function, primary dysmenorrhea or premenstrual syndrome, rheumatoid arthritis, COVID-19, painful statues, and HR-QOL. However, for many diseases, the conclusions remain uncertain.ConclusionThe available evidence suggests that curcumin is a safe medicinal agent that improves multiple clinical outcomes; however, the scientific quality of published studies needs to be improved.